O USO DAS MIDIAS DIGITAIS COMO FERRAMENTA DE DIVULGAÇÃO DA GESTÃO AMBIENTAL EMPRESARIAL: UMA RELAÇÃO ENTRE SUSTENTABILIDADE E LUCRATIVIDADE - Alvaro Costa Jardim Neto; Jéssica Cristina Jordão Sant'ana; Valdecir Cahoni Rodrigues (Universidade do Oeste Paulista, 2015)
Currently sustainability programs of organizations are directly related to the increase of its profitability. With more demanding and aware consumer companies have used these changes as a strategic form of disclosure of their practices in social media as a way to improve its image. The method used for this research was literature with the use of the main authors who address this topic. The objective was to demonstrate the benefits of sustainable practices for the disclosure of organizations through digital marketing. Through research it was found that there are several benefits such as improved image of the company, zero cost to the disclosure, more easily reach your target audience, etc.